Mineração de granito no município de vila pavão/es[1]: compreender o trabalho para pensar a formação - Daisy Moreira Cunha; Daniel Handan Triginelli (Universidade do Porto, 2013)
The paper presents the results of the research Working Relations and Conditions in the Granite Extraction in the city of Vila Pavão - ES: understand the work to think about the training, whose objective was to understand the working relations/conditions in the mineral sector, unveiling aspects related to the training of workers in granite quarries. The qualitative research was accomplished through the review of literature and documents, observation of workplaces in several companies and semi-structured interviews with workers of this sector in the northern region of Espírito Santo/Brazil. The results point to the strategic importance of the miners' work activity in the development of the mineral sector in the region. The effort to understand the working relations/conditions in the sector under research provided knowledge about the process of extraction, the vocational training on the job and other aspects regarding the human training of workers as miners.